IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM IN 21ST CENTURY LEARNING - Djoeaeriah, Neng Djodjoh; Sofyan Iskandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research aims to find out what 21st-century learning competencies are. 21st-century learning competencies are oriented toward thinking literacy, work skills, life skills, and the ability to master tools for work. This research uses a qualitative approach, describing and elaborating on 21st-century educational competencies. The data collection technique used in this research is library research. The research results show that implementing the Independent Learning Curriculum (KMB) in 21st-century learning is one solution to improve school learning quality. Implementing KMB allows teachers to facilitate a more interactive, fun, and practical student learning process. Apart from that, KMB can also help students to learn independently, collaborate with others, and develop critical and creative thinking skills. However, to implement KMB well, teachers must pay attention to several things, such as providing varied and exciting learning resources, a comfortable and conducive learning space, and a transparent and fair evaluation system.